1996
DOI: 10.1126/science.274.5289.961
|View full text |Cite
|
Sign up to set email alerts
|

Mg/Ca Thermometry in Coral Skeletons

Abstract: The magnesium-to-calcium (Mg/Ca) ratio of coral skeletons from Ishigaki Island, Ryukyu Islands, Japan, closely tracked sea surface temperature (SST) over an 8-year period. Measurements were made with the fast technique of inductively coupled plasma-atomic emission spectrometry. The variation of the coral Mg/Ca ratio with SST change is about four times that of the current, widely used coral strontium-to-calcium ratio. The temporal and geographic variation of the seawater Mg2+/Ca2+ ratio probably has little infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
196
3
6

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(225 citation statements)
references
References 11 publications
17
196
3
6
Order By: Relevance
“…Given the long residence time of Mg in ocean waters, it is unlikely that squid at the different locations experienced varying concentrations of dissolved Mg2+. Mitsuguchi et al (1996) reported that Mg/Ca ratios were positively correlated with temperature in coral skeletons, but it seems unlikely that the autumn-spawned cohort was consistently exposed to higher temperatures than the spring-spawned cohort ). However, differences in Mg and Mn content could be explained if organic content varied with growth rate and growth rate varied across cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Given the long residence time of Mg in ocean waters, it is unlikely that squid at the different locations experienced varying concentrations of dissolved Mg2+. Mitsuguchi et al (1996) reported that Mg/Ca ratios were positively correlated with temperature in coral skeletons, but it seems unlikely that the autumn-spawned cohort was consistently exposed to higher temperatures than the spring-spawned cohort ). However, differences in Mg and Mn content could be explained if organic content varied with growth rate and growth rate varied across cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…3c). As Mg/Ca is positively correlated with SST (Mitsuguchi et al 1996(Mitsuguchi et al , 2003, this rising trend may record the increase in SST from the 1930s. In contrast, the Mg/Ca series obtained from 10AR1 has no secular rising or declining trend from the 1930s (Fig.…”
Section: Coral Geochemical Records and Growth Ratesmentioning
confidence: 99%
“…Most of these are based on the temperature-dependent incorporation of divalent cations into coral skeletal aragonite. The use of coralline Sr/Ca ratios as a temperature proxy has received the most attention (Smith et al, 1979;Beck et al, 1992) though several other coral temperature proxies also have been proposed, most notably Mg/Ca ratios (Oomori et al, 1983;Mitsuguchi et al, 1996) and U/Ca ratios (Min et al, 1995;Shen and Dunbar, 1995). Other potential coral paleothermometers include B and F (Hart and Cohen, 1996) which occur as trace elements in seawater and coral ((1 ppm).…”
Section: Paleothermometrymentioning
confidence: 99%